Topical Anti-inflammatory Activity of Bangle (Zingiber cassumunar Roxb). Ethanolic Extract in Mice Induced By Carrageenan - Endang Dwi Wulansari; Subagus Wahyuono; Marchaban Marchaban; Sitarina Widyarini (Majalah Obat Tradisional, 2018)
Rhizome of bangle (Zingiber cassumunar Roxb.) is one of the materials that are traditionally used in the traditional preparation to maintain skin from redness. The content of chemical compound in bangle rhizomes has many benefits, including inhibition of the inflammatory processes. This study aims to determine the topical anti-inflammatory activity of ethanolic extract of bangle rhizomes in mice induced by carrageenan. Thirty five female Swiss mice were used in this study. Animals were divided into 7 group of five: normal group, carrageenan 2% group, carrageenan 2% group plus control of basis (Biocream®), carrageenan 2% group plus 2.5% hydrocortisone cream, and carrageenan 2% group plus cream of ethanolic extract of bangle rhizomes with the concentration of 1%, 2.5% and 5% w/w. Carrageenan 2% was injected subcutaneously in all treatment group except normal group. The skinfold thickness of mice was measured every 1 hour for 6 hours after carrageenan injection. Results of this study shows that there is a significant differences between treatment groups (p <0.05) compared to carrageenan 2% treated group. To conclude, ethanolic extract of bangle rhizomes has topical anti-inflammatory in mice induced by carrageenan.